An electrical cause of stridor: Pediatric vagal nerve stimulators. Issue 2 (February 2015) - Kelts, Gregory; O'Connor, Peter D.; Hussey, Richard W.; Maturo, Stephen
Abstract Vagal nerve stimulators (VNS) are surgically implantable medical devices which are approved by the food and drug administration (FDA) for treatment of medically refractory epilepsy in children. Two children with seizures disorders presented to the pediatric otolaryngology clinic with complaints of stridor and sleep apnea following implantation of VNS devices. Both children were evaluated with flexible laryngoscopy, direct laryngoscopy and bronchoscopy. The children were noted to have contraction of their vocal folds and supraglottis and the settings of their VNS were adjusted until no further contractions were noted. Each child had resolution of their symptoms following adjustment.